Psicología del testimonio en la verosimilitud credibilidad y fiabilidad de la declaración testimonial de la víctima menor de edad en procesos penales por violación sexual Iquitos 2018 - Gardini Taborga, Mayra (2023)
Psychology of the testimony in the credibility, credibility and reliability of the testimonial statement of the minor victim in criminal proceedings for rape, Iquitos 2018 had the general objective of determining how the Psychology of the Testimony explains the credibility, credibility and reliability of the testimonial statement of the victim, a minor, in criminal proceedings for rape in Iquitos, 2018. The research was mixed (consisting of a qualitative and quantitative variable) whose correlation between the variables of the general hypothesis was estimated by applying the chi square test. The research design used was Research-Action. The Documentary Analysis and the Survey were used as techniques for the systematic collection of data in the investigation. The results were that there was no significant relationship between the application of the psychology of testimony and the determination of the plausibility, credibility and reliability of the testimonial statement of the minor victim in criminal proceedings for rape in Iquitos, 2018. The main conclusion was that judges, prosecutors and lawyers show little knowledge about the application of the Psychology of Testimony to explain the testimonial statement of the minor victim of rape and since they are the main operators of criminal law and criminal procedure, this situation explains that there was not the proper application of the Psychology of Testimony regarding the processes for rape in the city of Iquitos, 2018.